2002
DOI: 10.1177/088740302237806
|View full text |Cite
|
Sign up to set email alerts
|

Help Wanted: A Survey of Employer Concerns About Hiring Ex-Convicts

Abstract: The majority (53%) of 62 Baltimore area employers surveyed were willing to hire an ex-offender described in a hypothetical scenario. Employers’greatest apprehensions concerned ex-offenders’ people skills and their customers’ discomfort if customers knew that an ex-convict worked for them. Also, the data show that employers’willingness to take advantage of a program with subsidized wages and their fear of being victimized were related to their degree of social contact with ex-convicts. These findings suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 10 publications
(9 reference statements)
4
70
2
1
Order By: Relevance
“…We began by developing an initial list of policy features based on existing policies as already described, and previous survey literature focusing on employers' preferences (Albright and Denq, 1996;Giguere and Dundes, 2002;Holzer, Raphael, and Stoll, 2004;Graffam, Shinkfield, and Hardcastle, 2008;Lukies, Graffam, and Shinkfield, 2011;Lageson, Vuolo, and Uggen, 2015). Then, as suggested by Coast et al (2012), we revised the list through prestudies and pretests.…”
Section: Survey Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We began by developing an initial list of policy features based on existing policies as already described, and previous survey literature focusing on employers' preferences (Albright and Denq, 1996;Giguere and Dundes, 2002;Holzer, Raphael, and Stoll, 2004;Graffam, Shinkfield, and Hardcastle, 2008;Lukies, Graffam, and Shinkfield, 2011;Lageson, Vuolo, and Uggen, 2015). Then, as suggested by Coast et al (2012), we revised the list through prestudies and pretests.…”
Section: Survey Developmentmentioning
confidence: 99%
“…We developed it by drawing from prior surveys or interviews of employers (Albright and Denq, 1996;Giguere and Dundes, 2002;Holzer, Raphael, and Stoll, 2004;Graffam, Shinkfield, and Hardcastle, 2008;Lukies, Graffam, and Shinkfield, 2011;Lageson, Vuolo, and Uggen, 2015) and the pretest interviews with human resources professionals and construction supervisors and executives overseeing large public and private construction projects.…”
Section: Follow-up Survey Questionsmentioning
confidence: 99%
“…Survey-based studies have shown that people who have had contact with exoffenders hold less negative attitudes towards ex-offenders than those who have had no past interaction with ex-offenders (Hirschfield and Piquero 2010). Other survey-based studies on employers' willingness to hire former criminals have shown that employers' fear of ex-offenders committing new crimes depends on whether employers have had any previous contact with ex-offenders: employers who had experienced previous contact with ex-offenders, frequently or occasionally, had little concern about whether ex-offenders would commit any new crimes (Giguere and Dundes 2002). Hence, if exposure to ex-offenders varies across different types of occupations, the acceptability of ex-offenders may very well vary across occupations as well.…”
Section: Conceptualizationmentioning
confidence: 99%
“…Employers consider whether the type of crime committed may relate to the type of position being applied for (Albright & Denq, 1996;Graffam et al, 2004), and whether the safety of themselves, their staff or customers is perceived to be at risk (Giguere & Dundes, 2002;Pager & Quillian, 2005).…”
Section: Introductionmentioning
confidence: 99%